Nifedipine degradation by an electro-oxidation process using titanium-based RuO2âIrO2âTiO2 mixed metal oxide electrode - Wirzal, M.D.H. (Springer Science and Business Media Deutschland GmbH, 2021)
The interest in new emerging pollutants (NEPs) does not only focus on the main compounds but also the degradation or intermediate products. It is important to have an effective primary treatment for the removal/degradation of NEPs from hospital and clinical wastewater to protect the environment. In this study, nifedipine degradation was performed by an electro-oxidation method using titanium-based mixed metal oxide (MMO) electrode. The determination of nifedipine was carried out by differential pulse voltammetry at hanging mercury drop electrode using BrittonâRobinson buffer (BRB). The nifedipine oxidation peak was observed at + 0.7Â V at a scan rate of 20Â mVÂ sâ1 in BRB pH 8. Titanium-based electrodes with different metal oxide compositions were assessed as an anode material for nifedipine degradation as follows: TiO2/Ti, IrO2âTiO2/Ti, RuO2âTiO2/Ti, and IrO2âRuO2âTiO2/Ti. The electro-oxidation of nifedipine was monitored using cyclic voltammetric techniques, and the degradation intermediates were confirmed using LCâMS. Approximately 65â83 of nifedipine degradation was achieved using RuO2âTiO2/Ti and IrO2âTiO2/Ti electrodes. Interestingly, RuO2âIrO2âTiO2 electrode showed complete (100) electro-oxidation of nifedipine at 30Â min. Two nifedipine degradation intermediates were identified, namely 5-methoxycarbonyl-2,6-dimethyl-4-phenyl-1,4-dihydropyridine-3-carboxylic acid (compound I) and 2,6-dimethyl-4-phenyl-1,4-dihydropyridine-3,5-dicarbaldehyde (compound II) during the electro-oxidation process using RuO2âIrO2âTiO2 electrode. Finally, the degradation pathway of nifedipine by MMO electrode was proposed. This is the first report on the nifedipine degradation using MMO titanium electrode by the electro-oxidation process. Â© 2020, Institute of Chemistry, Slovak Academy of Sciences.